2023
DOI: 10.1097/mog.0000000000000971
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal bacterial overgrowth: current update

Hammad Zafar,
Brenda Jimenez,
Alison Schneider

Abstract: Purpose of review This article aims to provide an up-to-date review of small intestinal bacterial overgrowth (SIBO), including etiology and risk factors, clinical manifestations, diagnostic evaluation for suspected SIBO, and therapeutic options. Recent findings Recent advances in breath testing, capsule and urine-based testing have opened new avenues and improved diagnostic yield of SIBO. Nonantibiotic-based treatment strategies have shown promising res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Antimicrobial agents, such as rifaximin (550 mg, three times a day), metronidazole (250–500 mg, three times a day), or doxycycline (100 mg, twice a day), administered periodically may be helpful in neutralizing the effects of SIBO, a condition associated with various gastrointestinal symptoms, as well as nutrient deficiencies, and weight loss [ 114 , 115 ]. It has recently been shown that the bioavailability of oral antibiotics was higher than expected in patients who have suffered a loss of their anatomical surface area for absorption [ 116 ].…”
Section: Short Bowel Syndrome (Sbs)mentioning
confidence: 99%
“…Antimicrobial agents, such as rifaximin (550 mg, three times a day), metronidazole (250–500 mg, three times a day), or doxycycline (100 mg, twice a day), administered periodically may be helpful in neutralizing the effects of SIBO, a condition associated with various gastrointestinal symptoms, as well as nutrient deficiencies, and weight loss [ 114 , 115 ]. It has recently been shown that the bioavailability of oral antibiotics was higher than expected in patients who have suffered a loss of their anatomical surface area for absorption [ 116 ].…”
Section: Short Bowel Syndrome (Sbs)mentioning
confidence: 99%
“…There is also an important role in the process for small intestinal bacterial overgrowth (SIBO), which is defined as an increase in the content of bacteria in the small intestine of more than 100,000 cells per mL [37][38][39][40]. An increase in the bacterial population of the small intestine also can lead to bacterial translocation, promoting liver fibrosis.…”
Section: Gut Microbiota In Normal and Pathological Conditionsmentioning
confidence: 99%